(3QaY GdedGe Yf GdCFeI GdCYdGes - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s
(3ChdgG (B:s
(3hHYO ajLH Ydi GdeSdejf HYO ehGdGI Gddg hQShdg ehGdGI GdeDefjf ceG fWb Hg GdbQBf s
(3BNQgG (B:s
(3adG HO Cf fDef HGdcJGH cdg hfJHY eG CfRd EdjfG ef QHfG LejYg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B911s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeJMa GdYQGbi (B(976) s
Keywords: (3Gdabg GdMfHdjs